PENGARUH PENGGUNAAN FITUR JAKLAPOR APLIKASI JAKI TERHADAP KEPUASAN MASYARAKAT PADA KINERJA PELAYANAN PUBLIK PEMPROV DKI JAKARTA - Firly Laras Sukma, (2021)
In order to manage information and communication technology for a betterr developement of Jakarta, the DKI Jakarta's Provincial Goverment established Jakarta Smart City to optimized the use of information and communication technology in Jakarta. This can be seen with the creation of a public service application, namely JAKI, and there is JakLapor feature that can be used by the public to report various non-emergency problems that found in Jakarta. The purpose of this research is to determine if there is significant influence of using JakLapor feature on public satisfaction of performance of DKI Jakarta Provincial Goverment's Public Service. The result of this research state that there is a significant influence between the use of JakLapor feature on public satisfaction of performance of DKI Jakarta Provincial Goverment's Public Service. This is such a strong and positive influence, 51,7%. This research uses a quantitative approach with a descriptive type. The data collection method used is through quesionnares to respondents.